Simulation of the Ontogeny of Social Jet Lag: A Shift in Just One of the Parameters of a Model of Sleep-Wake Regulating Process Accounts for the Delay of Sleep Phase Across Adolescence - Putilov, Arcady A.; Verevkin, Evgeniy G. (Frontiers in Physiology, 2018)
The term “social jet lag” was introduced for defining the conflict between social and biological clocks due to the general practice of shifting weekday risetime on early morning hours. The phase delay of the sleep-wake cycle during adolescence is one of the most remarkable features of the ontogenesis of sleep that is incompatible with early school start times. It is not clear why post-pubertal teens are often more susceptible to social jet lag than either children or young adults. It was previously proposed that the process of accumulation of sleep pressure during wakefulness is slowing down in post-pubertal teens to allow them to stay awake for a longer period of time thus causing the delay of their bedtime. In order to examine this proposition, we traced the ontogeny of social jet lag using sleep times reported for 190 samples of study participants of different ages as an input to a model of sleep-wake regulatory process. The simulations suggested that adolescents’ susceptibility to social jet lag might generally be highest when their maturating organisms have sleep duration that is neither too short, nor too long in addition to sleep phase that is already late, but not the latest yet. The simulations also allowed the conclusion that a gradual change in just one of the model’s parameters, the time constant of wakefulness phase of the sleep-wake regulatory process, might explain the association of the transition between childhood and adulthood with the prolongation of time staying awake and reduction of sleep duration.